Municipal governance of the sharing economy sectors: global insights - Voytenko Palgan, Yuliya; Mont, Oksana (Understanding the Urban Sharing Economy, 2025)
The sharing economy generates many benefits for cities and their citizens. However, it also causes numerous economic, social and environmental challenges, which are the reasons cities develop various policies and regulations. Previous research has explored municipal regulations across cities and countries but often overlooked alternative governance mechanisms. Our earlier work highlighted the need to systematically explore variations in governance approaches adopted by municipalities towards the sharing economy's sectors like accommodation, mobility and physical goods. This chapter compares municipal governance in ten cities, Amsterdam, Berlin, Gothenburg, London, Malmö, Melbourne, San Francisco, Seoul, Shanghai and Toronto, according to a comprehensive framework of municipal governance comprising five mechanisms and 11 roles. Empirical evidence comes from 212 semi-structured interviews, ten mobile research labs, nine stakeholder workshops, three focus groups, and a review of academic and grey literature. This chapter unpacks why municipal governance of the sharing economy varies across cities and sectors, introducing a framework for categorising contextual factors shaping municipal engagement with sharing organisations.
Keywords: sharing economy; sharing cities; municipal governance; municipality; framework; city